Continuance intention to use digital payments in mitigating the spread of COVID-19 virus - Singha Chaveesuk; Bilal Khalid; Wornchanok Chaiyasoonthorn (International Journal of Data and Network Science, 2022)
This study investigated the continuous intention to use digital payment solutions in online transactions to mitigate the spread of the COVID-19 virus. Primary data was collected from individuals using digital payment systems in Bangkok, Thailand using a structured questionnaire from a total of 400 respondents. The study adopted the Technology Acceptance Model (TAM). Data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) in AMOS 26. The results revealed that factors that significantly affected continuous intention to use digital payments were perceived ease of use, satisfaction, attitude, and social distancing. Satisfaction mediated the effects of perceived usefulness, perceived ease of use, and social distancing on continuous intention to use. Attitude mediated the effect of perceived usefulness on continuous intention to use. The study recommends that concerned policymakers and institutions should consider users’ satisfaction, social distancing, and perceived ease of use when developing digital payment systems.
Keywords: Technology Adoption and User Behaviour; Organizational and Employee Performance; COVID-19 Pandemic Impacts